Sequence analysis of genome segments S5 and S10 of Mal de Río Cuarto virus (Fijivirus, Reoviridae) - Distefano, Ana Julia; Hopp, Horacio Esteban; Del Vas, Mariana (Springer, 2023)
Mal de Río Cuarto virus (MRCV) was recently described as a new species of the genus Fijivirus, family Reoviridae. The nucleotide sequence of two MRCV genome segments was determined. MRCV S5 and S10 were predicted to encode proteins of 106.9 and 63.5 kDa respectively. The protein coded by MRCV S5 had 62.8% and 35.7% identity to fijiviruses RBSDV S5 and FDV S5 coded proteins, and contained a rarely reported type-1 C-terminal peroxisomal targeting signal. The protein coded by MRCV S10 had identity levels of 72.4% and 21.7% to the major outer capsid proteins of fijiviruses RBSDV S10 and NLRV S8.